GSNO as a Modulator of Vascular Tone in Human Saphenous Veins: Potential Implications for Graft Spasm - Deniz Kaleli Durman; Nurdan Dağtekin; Erkan Civelek; Taner İyigün; Önder Teskin; Birsel Sönmez Uydeş Doğan (Life)
S-nitrosoglutathione (GSNO), a promising S-nitrosothiol, has been recognized for its ability to modulate vascular tone through its vasodilatory, antiplatelet, and antiproliferative effects. However, data on its vasodilatory effects in human vessels remain limited, and its mechanisms of action have yet to be fully elucidated. In this study, we aimed to investigate the vasorelaxant effect of GSNO and its underlying mechanisms, with particular focus on the soluble guanylate cyclase (sGC)/nitric oxide (NO) pathway and potassium channels in isolated human saphenous veins (SVs) obtained from patients undergoing coronary artery bypass grafting (CABG). GSNO (10−8–10−4 M) produced concentration-dependent relaxations in SV rings precontracted with phenylephrine. These relaxations were unaffected by NO synthase inhibition with L-NAME (10−4 M, 30 min) or NO scavenging with PTIO (10−4 M, 30 min), but were significantly reduced by the sGC inhibitor, ODQ (10−5 M, 30 min). Inhibition of ATP-sensitive (glibenclamid; 10−5 M, 30 min.), high-conductance Ca2+-activated (charybdotoxin; 10−7 M, 30 min), small-conductance Ca2+-activated (apamin; 10−6 M, 30 min), or voltage-dependent (4-aminopyridine; 10−3 M, 30 min) potassium channels did not alter the maximum relaxant responses to GSNO. Furthermore, pretreatment with GSNO (10−4 M, 30 min) significantly attenuated both the contractile response and sensitivity to phenylephrine. Collectively, these findings demonstrate that GSNO exerts acute vasorelaxant and modulatory effects in human SV primarily via cGMP-dependent mechanisms, highlighting its potential as a local therapeutic agent for preventing graft spasm in CABG.